(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Alzheimer’s disease, known as AD, is the most common form of dementia, affecting approximately 35 million people globally and progressing over time. Effective treatments and preventive measures are currently lacking, despite significant advancements in understanding its molecular pathways since its initial description in 1907. Research has highlighted connections between cognitive function, caregiver burden, and Behavioral and Psychological Symptoms of Dementia (BPSD). However, the relationship between caregiver burden and BPSD in community-dwelling Alzheimer’s patients remains unclear. This review aims to explore the pathophysiology of Alzheimer’s disease, behavioral manifestations in affected individuals, and its comorbidities. Additionally, it examines the impact of COVID-19 on Alzheimer’s patients and underscores the importance of digital health, clinical outcomes, policy frameworks, and basic science. Recommendations for future research and challenges in leveraging gender and sex differences in Alzheimer’s research are also addressed, alongside insights into disease biomarkers, drug targets, and network biology methodologies for identifying new biomarkers and therapies.